Online media and narrative hegemony: Discourse network analysis of the 2025 Pertamina case - Astuti, Yanti Dwi; Adeni, Adeni (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
This article examines how narrative dominance is constructed and contested in Indonesian online media coverage of the 2025 Pertamina mega corruption scandal. The study applies Discourse Network Analysis (DNA) to map relational configurations between actors and claims. The dataset consists of 110 attributed statements extracted from ten high-traffic Indonesian online news outlets published between February and March 2025. The study converts quoted statements into actor–claim networks and analyzes them using centrality and modularity measures. The results reveal a polarized discourse structure with four major communities (modularity Q = 0.47). A technocratic bloc dominates the network, accounting for 38% of statements and securing a disproportionate share of eigenvector centrality, while accountability-oriented actors remain structurally peripheral. The top ten central actors, including the Ministry of Energy, Pertamina, KPK, CNNIndonesia, Tempo.co, and ICW, function as anchors, brokers, or amplifiers that shape discursive visibility and legitimacy. The findings demonstrate how technocratic framing functions as a hegemonic anchor that reframes corruption as a managerial issue rather than a systemic crime. Practically, the study highlights the need for media policy reforms that strengthen watchdog amplification, diversify authoritative sources, and prevent excessive reliance on technocratic legitimation in corruption reporting. DNA thus offers a powerful methodological framework for diagnosing discursive power imbalances in digital democracies. ***** Artikel ini mengkaji bagaimana dominasi narasi dibangun dan diperebutkan dalam pemberitaan media daring Indonesia mengenai skandal mega korupsi Pertamina tahun 2025. Penelitian ini menerapkan Discourse Network Analysis (DNA) untuk memetakan konfigurasi relasional antara aktor dan klaim wacana. Dataset penelitian terdiri atas 110 pernyataan teratribusi yang diekstraksi dari sepuluh media daring Indonesia dengan tingkat trafik tinggi yang diterbitkan antara Februari hingga Maret 2025. Pernyataan-pernyataan yang dikutip dikonversi menjadi jaringan aktor–klaim dan dianalisis menggunakan ukuran sentralitas dan modularitas. Hasil analisis menunjukkan struktur wacana yang terpolarisasi dengan empat komunitas utama (modularitas Q = 0,47). Blok teknokratis mendominasi jaringan dengan menyumbang 38% dari seluruh pernyataan serta menguasai proporsi sentralitas eigenvektor yang tidak seimbang, sementara aktor-aktor yang berorientasi pada akuntabilitas tetap berada di posisi perifer secara struktural. Sepuluh aktor paling sentral termasuk Kementerian Energi dan Sumber Daya Mineral Republik Indonesia, Pertamina, KPK, CNNIndonesia, Tempo.co, dan ICW, berfungsi sebagai jangkar, perantara, atau penguat yang membentuk visibilitas dan legitimasi wacana. Temuan ini menunjukkan bagaimana pembingkaian teknokratis berfungsi sebagai jangkar hegemonik yang membingkai ulang korupsi sebagai persoalan manajerial alih-alih sebagai kejahatan sistemik. Secara praktis, penelitian ini menegaskan perlunya reformasi kebijakan media yang memperkuat peran pengawasan, memperluas keberagaman sumber otoritatif, serta mencegah ketergantungan berlebihan pada legitimasi teknokratis dalam pemberitaan korupsi. Dengan demikian, DNA menawarkan kerangka metodologis untuk mendiagnosis ketimpangan kekuasaan wacana dalam demokrasi digital.